The Concept of Islamic Education to the Human Quality in Islamic Universities - Amrullah, Abdul Malik Karim; Segaf, Segaf (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1148, 2020)
Best Islamic universities in the world are fascinating to be study their contribution to human civilization. However the recent Islamic University underperform to the glorious earlier period, as for the lack of intellectual moslems, intellectual traditions product and quality standards to solve the education problematic worldwide. The objective of this study is to determine the concept of Islamic education, which imply the best practices of best Islamic universities management in the world. This study uses library research approach with descriptive analysis. The quality of Islamic universities cannot be separated from the concept of Islamic education that develop insan kamil (the perfect man) who has the power of reasoning, mental, physical and spiritual that eventually evolved on strengthening academic-reinforcement to support the concept of insan kamil.